Effect of Adalimumab on Peripheral Blood Mononuclear Cells in Non-Infectious Uveitis. (17th February 2019) - Walscheid, Karoline; Weinhage, Toni; Foell, Dirk; Heinz, Carsten; Kasper, Maren; Heiligenhaus, Arnd
ABSTRACT: Purpose: This study analyzed the effect of adalimumab on peripheral blood mononuclear cells (PBMCs) in uveitis. Methods: PBMCs and serum S100A12 levels from 14 uveitis patients and 28 healthy controls were analyzed. Patient samples were taken before (w0), and 6 (w6) and 12 (w12) weeks after initiation of adalimumab therapy. Results: Monocytes expressing CD124, CD86, CD39, CD115, and MHCII were decreased in patients. Adalimumab induced CD86+ and CD39+ monocytes, and further decreased the frequency of MHCII- and CD124-positive cells. Patients (w0) had increased percentages of Th1-, Th17-, and Th2 cells and T cell subsets showed a pro-inflammatory polarization ( p = 0.02 ratio Th17/Treg patients w0 vs controls), which was reduced upon adalimumab treatment ( p = 0.05 w0 vs w6). S100A12 levels were increased in patients ( p = 0.02) and reduced under treatment ( p = 0.02 for w6/w12). Conclusions: The phenotype of PBMCs from uveitis patients is modified upon adalimumab treatment. Serum S100A12 levels reflect the systemic immune response.